DESIGN OF A WEB-BASED STUDENT ACTIVITY FEASIBILITY DETERMINATION APPLICATION USING THE ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (CASE STUDY : POLITEKNIK SUKABUMI) - Pamungkas, Rio Andrian; Rahayu, Samirah (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2025)
The rapid development of information technology has encouraged universities to manage student activities more effectively, efficiently, and measurably. The process of determining the feasibility of student activities at Politeknik Sukabumi is still conducted manually, which may lead to subjective assessments, delays in approval, and a lack of transparency. This final project designs a web-based information system featuring activity data management, criteria, subcriteria, and automated calculations using the Analytical Hierarchy Process (AHP) method. The AHP implementation allows priority weights to be calculated through pairwise comparisons between criteria, producing feasibility scores that are consistent and objective. The system was developed using the Laravel framework and tested using blackbox testing to ensure all features function as intended. Test results show that all main functions operate as expected, while the AHP algorithm achieves 100% calculation consistency, indicating stability and accuracy in generating recommendations for student activity feasibility.